2014
DOI: 10.1128/cvi.00375-14
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of the Safety of an Influenza A(H1N1) Vaccine in Pregnant Chinese Women

Abstract: To monitor and evaluate the safety of the influenza A(H1N1) vaccine in pregnant women and its influence on the fetus and neonate, we performed a prospective study in which 122 pregnant Chinese women who received the influenza A(H1N1) vaccine and 104 pregnant women who did not receive any vaccine (serving as controls) were observed. The results indicated that the seroconversion rate in the vaccinated group was 90.4% (95% confidence interval [CI], 82.6% to 95.5%). The rate of adverse events following immunizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The results are presented in Figure . In total, 100 studies were included in the review . Several studies provided data on maternal morbidity and mortality, pregnancy outcome and treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are presented in Figure . In total, 100 studies were included in the review . Several studies provided data on maternal morbidity and mortality, pregnancy outcome and treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This good response to vaccination results in a reduction of approximately half of maternal influenza virus infections . No adverse effects of vaccination on pregnancy outcome have been reported . Whether vaccination has a positive effect on pregnancy outcome is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Although experience with the use of IIVs during pregnancy is substantial, data specifically reflecting administration of influenza vaccines during the first trimester are relatively limited (see Safety of Influenza Vaccines: Pregnant Women and Neonates in the supplementary Background Document). Most studies have not noted an association between influenza vaccination and adverse pregnancy outcomes, including spontaneous abortion (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). One observational Vaccine Safety Datalink (VSD) study conducted during the 2010-11 and 2011-12 seasons noted an association between receipt of IIV containing influenza A(H1N1)pdm09 and risk for spontaneous abortion (miscarriage) in the 28 days after IIV, when an H1N1pdm09-containing vaccine had also been received the previous season (51).…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Three studies 21,26,33 involving 8025 patients in the exposed group and 55 843 women in the control group reported the rate of spontaneous abortion after H1N1 vaccination. The pooled result showed that the difference between the vaccinated and unvaccinated T A B L E 2 Risk of bias in the included studies assessed using the Newcastle-Ottawa scale.…”
Section: Spontaneous Abortionmentioning
confidence: 99%